2022
DOI: 10.3390/ijerph191610030
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Analysis of Diabetes-Related Hospitalization in Poland before and during the COVID-19 Pandemic, 2014–2020

Abstract: Diabetes is one of the most common chronic diseases worldwide. The study aimed to present an epidemiological analysis of hospitalization related to diabetes mellitus in Poland between 2014 and 2020 as well as to analyze changes in diabetes-related hospital admissions before and during the COVID-19 pandemic. This study is a retrospective analysis of the national registry dataset of hospital discharge reports on diabetes-related hospitalizations in Poland between 2014 and 2020. The number of diabetes-related hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
9
0
3
Order By: Relevance
“…According to the WHO estimates, partial or complete suspension of regular health services in the field of hypertension, diabetes, and diabetes-related complications, cancer, and cardiovascular outbreaks due to the COVID-19 pandemic were observed in 53% of countries worldwide (13,33). Previously published data indicated a markable decrease in urological and diabetes care utilization in Poland (23)(24)(25). Findings from this study showed that half of the adults in Poland declared that they had to visit a doctor, but this was not possible due to barriers to accessing health services during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the WHO estimates, partial or complete suspension of regular health services in the field of hypertension, diabetes, and diabetes-related complications, cancer, and cardiovascular outbreaks due to the COVID-19 pandemic were observed in 53% of countries worldwide (13,33). Previously published data indicated a markable decrease in urological and diabetes care utilization in Poland (23)(24)(25). Findings from this study showed that half of the adults in Poland declared that they had to visit a doctor, but this was not possible due to barriers to accessing health services during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in healthcare uptake during the COVID-19 pandemic may contribute to a health debt, and thus delay the diagnosis and treatment of diseases ( 22 ). Moreover, barriers to accessing health services during the pandemic may deepen health inequalities ( 23 ). However, there are limited data on health services during the COVID-19 pandemic in Poland, mostly focused on hospital admissions ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study also underline the positive influence of having a family member with diabetes on the level of awareness of diabetes among other family members. The COVID-19 pandemic has a negative impact on diabetes care in Poland ( 13 , 46 ), so public health interventions aimed to increase the level of public awareness of diabetes are needed to reduce the diabetes burden in Poland. Further studies should analyze the impact of the health system and diabetes education provided by healthcare workers on public awareness of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that DM plays a key role in global morbidity and mortality [ 9 ]. Worldwide in 2019, before the outbreak of the SARS-CoV-2 infection, nearly 463 million people aged between 20 and 79 had diabetes as comorbidity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%